THE RELATIONSHIP BETWEEN LEVELS OF KNOWLEDGE WITH BEHAVIOR OF PROPER HAND-WASHING IN THE FIFTH GRADE STUDENTS MARDIYUANA ELEMENTARY SCHOOL BOGOR: HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU MENCUCI TANGAN YANG BENAR PADA SISWA KELAS V DI SD MARDIYUANA BOGOR - Bunga Bunga Oktora (Jurnal Ilmiah Wijaya, 2019)
Hand washing is the process of removing dirt and dust mechanically from the skin of both hands using soap and water. Hand washing is often considered a trivial thing in the community, even though hand washing can contribute to improving public health status.Based on the phenomenon, it can be seen that school-age children have a habit of not paying attention to the need for hand washing in daily life, especially when in the school environment.National hand washing behavior problems in 2013 were only 47.0% who behaved properly in hand washing.Data in Indonesia reports that in DKI Jakarta the highest place for good hand washing behavior is as much (59.2%), in Central Java as much (49.5%), East Java as much (48.1%) and in West Java (45.7%). Knowing the relationship between levels of knowledge with behavior of proper hand-washing in the fifth grade students at SDN Mardiyuana, Bogor 2017. This research type is analytic descriptive research with cross sectional research design. The sampling method uses total sampling with the population of fifth grade students. The Data collection was obtained from distributing questionnaires to the students by observing handwashing behavior, and the data were analyzed using chi square test. From the statement above, the research results showed that a good level of knowledge with proper hand washing behavior reached 19 respondents (55.9%), then 11 respondents reached (32.4%) and less as many as 4 respondents (11.8%). So that, The results of bivariate analysis with the chi square test showed p value 0.037 ≤ 0.05. There is a relationship between the level of knowledge and proper handwashing behavior in fifth grade students at SDN Mardiyuana, Bogor in 2017. In conclusion, Based on the results of the research, fifth grade students need to increase their knowledge about hand washing and improve their habit of washing hands properly and correctly.